Volumetric, acoustic and spectroscopic studies (FT-IR) of trisodium (TSC) and tripotassium citrate (TPC) in aqueous solution of ionic liquid 1-butyl-3-methylimidazolium tetrafluoro borate [C4mim][BF4] at different temperatures. (January 2018) - Kumar, Harsh; Katal, Arjuna
Highlights: New densities and speeds of sound of citrate salts in aqueous [C4 MIM][BF4 ] solutions. Positive apparent molar volumes predict dominance of solute-solvent interactions. Pair and triplet interaction coefficients predict pair wise interactions in mixtures. Infrared spectral analysis of mixtures to analyze the interactions. Shift in the wavenumber predicts the interactions between [C4 MIM][BF4 ]in citrate salts. Abstract: In this work, density ρ, and speed of sound u, for citrate salts trisodium citrate (TSC) and tripotassium citrate (TPC) have been measured in (0.005, 0.01, 0.03 and 0.05) mol·kg −1 aqueous solution of ionic liquid 1-butyl-3-methylimidazolium tetrafluoro borate ([C4 mim][BF4 ]) at different temperatures T = (288.15, 293.15, 298.15, 303.15, 308.15) K at experimental pressure p = 0.1 MPa. Different parameters such as apparent molar volume (Vϕ ), partial molar volume ( Vϕ 0 ), and standard partial molar volumes of transfer ( ΔVϕ 0 ) have been calculated by using the experimental density data. From experimental speed of sound data apparent molar isentropic compression ( Kϕ, s ), partial molar isentropic compression ( K ϕ, s o ), and partial molar isentropic compression of transfer ( Δ K ϕ, s o ) have been calculated. The pair and triplet interaction coefficients have been calculated from transfer parameters. Infrared spectral studies have also been carried out for the present mixtures. Work is mainly concerned with the study of the interactions present in the mixtures of trisodium citrate and tripotassium citrate in aqueous solutions of ionic liquid 1-butyl-3-methylimidazolium tetrafluoro borate [C4 mim][BF4 ].